NANOPARTIKEL SINTESIS HIJAU BERBASIS SENYAWA ALAMI SEBAGAI PLATFORM INOVATIF DALAM TERAPI INFEKSI BAKTERI: LITERATURE REVIEW - Afni, Nur; Kartika, Andi Eka (Illea : Journal of Health Sciences, Public Health and Medicine, 2025)
Green synthesis of nanoparticles derived from natural compounds has emerged as a promising strategy to address increasing bacterial infections and antibiotic resistance. Unlike conventional methods that rely on toxic chemicals and high energy processes, this eco-friendly approach uses plant extracts as reducing and stabilizing agents, producing safer and more biocompatible nanoparticles. This narrative review summarizes recent findings on biosynthetic approaches, physicochemical characteristics, and antibacterial mechanisms demonstrated in experimental studies. Relevant articles published between 2015 and 2025 were retrieved from ScienceDirect, PubMed, and Google Scholar using defined eligibility criteria. The synthesis commonly produces silver, gold, or zinc oxide nanoparticles with nanoscale size (<100 nm) and high colloidal stability. These nanoparticles exhibit potent antibacterial activity through multimodal pathways, including membrane disruption, oxidative stress induction, and biofilm inhibition, including against multidrug-resistant pathogens. Overall, green-synthesized nanoparticles represent a promising and sustainable platform for antibacterial therapy; however, further standardization, toxicity evaluation, and preclinical validation are required before translation to clinical applications.